2020
DOI: 10.3390/nano10071321
|View full text |Cite
|
Sign up to set email alerts
|

ZnO Nano-Particles Production Intensification by Means of a Spinning Disk Reactor

Abstract: Zinc Oxide is widely used in many industrial sectors, ranging from photocatalysis, rubber, ceramic, medicine, and pigment, to food and cream additive. The global market is estimated to be USD 3600M yearly, with a global production of 10 Mt. In novel applications, size and shape may sensibly increase the efficiency and a new nano-ZnO market is taking the lead (USD 2000M yearly with a capacity of 1 Mt and an expected Compound Annual Growth Rate of 20%/year). The aim of this work was to investigate the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 52 publications
0
12
0
Order By: Relevance
“…Available sources suggest that the production and use of ZnO nanoparticles are increasing, rising from ≈550 000 kg in 2012 [ 51 ] to ≈1 600 000 kg in 2014, [ 39 ] with the estimated current global production in the range of 10 000 000 kg. [ 52 ] Therefore, elevated concentrations of ZnO in wastewaters have been described as inevitable in the near future. [ 53 ] Here, it was shown that a significant fraction of ZnO nanomaterials was rapidly sulfided during their incubation in influent water.…”
Section: Resultsmentioning
confidence: 99%
“…Available sources suggest that the production and use of ZnO nanoparticles are increasing, rising from ≈550 000 kg in 2012 [ 51 ] to ≈1 600 000 kg in 2014, [ 39 ] with the estimated current global production in the range of 10 000 000 kg. [ 52 ] Therefore, elevated concentrations of ZnO in wastewaters have been described as inevitable in the near future. [ 53 ] Here, it was shown that a significant fraction of ZnO nanomaterials was rapidly sulfided during their incubation in influent water.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike SiO 2 ENMs, however, Ag ENMs have been studied broadly [27]. Among the most threatening ENMs are ZnO NPs, with an annual global production of 10 Mt [47]. About ten percent of this production is released into the environment and 95% of it enters the aquatic system, accumulating in sediments [48].…”
Section: Synthesis Properties and Nature Of Npsmentioning
confidence: 99%
“…The bottom-up technologies are the most widely adopted in lab-to-pilot scale applications, whereas the top-down ones may present notable advantages for industrial scale productions. However, to achieve reproducible and homogeneous nanoparticles a number of innovative process units have been developed by various researchers, taking advantage of the particular geometry and fluid-dynamic conditions established inside the specific unit [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…The authors that contributed to this Special Issue well report, by their work, how the process intensification philosophy can be adopted for the production of nanoparticles of great interest in various industrial and civil applications. The production of zinc oxide [3] and starch [6] nanoparticles, by means of a spinning disk reactor represent a remarkable example of intensified production in the nano-size world. The spinning disk reactor represents one of the most promising PI technologies for the heat and mass transfer rate enhancement, obtained through centrifugal fields generated in the thin liquid film on the reactor disk by the rotation action.…”
mentioning
confidence: 99%